INDUCTION OF MORAL WISDOM AND ITS RECENT DEVELOPMENT IN PEDAGOGICAL STRATEGIES - Jayabalan, Rajan (PEOPLE: International Journal of Social Sciences, 2018)
In the era of Millennium, How the pedagogy of teaching has evolved? Do we teach the wisdom of moral values and tolerance? If ‘yes’why the gun shootings at Orlando and Texas has gone on rampage in America. The citizens of the modern world exhibit more intolerance rather adhering to temperance and tolerance. Through the lens of in-depth introspection, we need to analyse -especially the teaching fraternity: What are the essentials required to design pedagogies that shall assert Peace building and Moral Wisdom? In recent times, were the pedagogical reflections of peace and moral standards inducted and consciously taught in the teaching standards? If one say ,that considerable importance has been given in framing the educational course structure in coherence with Peace Building, Moral-Values and Humanity, then why the culture of terrorism in Syria, Kashmir and Israel- Palestine and hatred between neighbouring nations; such as India – Pakistan, North Korea- South Korea had taken its course so violently?